1999
DOI: 10.1093/genetics/153.2.933
|View full text |Cite
|
Sign up to set email alerts
|

The mac1 Mutation Alters the Developmental Fate of the Hypodermal Cells and Their Cellular Progeny in the Maize Anther

Abstract: In angiosperm ovules and anthers, the hypodermal cell layer provides the progenitors of meiocytes. We have previously reported that the multiple archesporial cells1 (mac1) mutation identifies a gene that plays an important role in the switch of the hypodermal cells from the vegetative pathway to the meiotic (sporogenous) pathway in maize ovules. Here we report that the mac1 mutation alters the developmental fate of the hypodermal cells of the maize anther. In a normal anther a hypodermal cell divides periclina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(3 citation statements)
references
References 20 publications
0
0
0
1
Order By: Relevance
“…Moreover, auxin is one of the mobile biochemical cues likely coordinating MMC and ovule growth. Other candidate coordinating signals include TPD1/MAC1 (Sheridan et al, 1996;Sheridan et al, 1999;Wang et al, 2012) and small RNAs (Komiya et al, 2014;Fei et al, 2016) shown to act in grasses to control germ cell fate. These biochemical cues act in concert with mechanical forces generated by the differential growth of the ovule cells connected through their walls of different material anisotropies.…”
Section: Coordination Of Anisotropic Growth Of the MMC And Ovulementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, auxin is one of the mobile biochemical cues likely coordinating MMC and ovule growth. Other candidate coordinating signals include TPD1/MAC1 (Sheridan et al, 1996;Sheridan et al, 1999;Wang et al, 2012) and small RNAs (Komiya et al, 2014;Fei et al, 2016) shown to act in grasses to control germ cell fate. These biochemical cues act in concert with mechanical forces generated by the differential growth of the ovule cells connected through their walls of different material anisotropies.…”
Section: Coordination Of Anisotropic Growth Of the MMC And Ovulementioning
confidence: 99%
“…Some of these pathways are remarkably conserved between Arabidopsis and grasses; for example, the RNA-directed DNA methylation (RdDM) pathway acts to control MMC singleness in both Arabidopsis and maize (Garcia-Aguilar et al, 2010;Petrella et al, 2021;Jiang & Zheng, 2022). Similarly, a signaling module involving the receptor EXTRA SPOROGENOUS CELLS 1/EXCESS MICROSPOROCYTES 1 (EXS1/EMS1) and its ligand TAPETUM DETERMINANT 1 (TPD1) restricts MMC number in maize and rice and pollen mother cell number in Arabidopsis (Sheridan et al, 1996;Sheridan et al, 1999;Zhao et al, 2002;Nonomura et al, 2003;Yang et al, 2003;Zhao et al, 2008;Wang et al, 2012). Also, mutations in ERECTA-like receptors generate multiple MMCs in both Arabidopsis (Hou et al, 2021) and rice (Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…abortion mechanism of GMS line in sesame. Keywords: Sesame (Sesamum indicum L.); Genetic male sterility; Microsporogenesis; Ultrastructure; TEM 芝麻(Sesamum indicum L., 2n=26)属于胡麻科芝 麻属, 是世界上重要的油料作物之一。1945 年印度 学者 Pal 首次报道了芝麻的杂种优势 [1] , 随后许多学 者研究证实芝麻品种间杂交 F 1 在产量方面杂种优势 尤为明显 [2] , 在品质、 抗逆性等方面也具有较强的超 标优势 [3] 。1982 年 Osman 与 Yermanos [4] 报道了第一 个可利用的芝麻核雄性不育材料, 并认为核雄性不 育性状受一对隐性基因控制。1983 年河南省芝麻研 究中心将其引入后, 通过回交改良选育出国内外第 一个有实用价值的核雄性不育系 ms86-1, 并应用于 二系杂交制种 [5] , 但二系制种须在初花期拔除一半 可育株, 存在工作量大、纯度无法保证等问题而难 以在生产上大面积应用。因此, 深入研究核雄性不 育机理, 改进杂交制种方法, 对芝麻杂种优势利用 具有重要意义。高洪善等 [6] 照拟南芥、 水稻等作物花粉发育过程的分期方法 [7][8][9] , 因的精确调控, 分化过程的异常可能注定小孢子败 育的命运。近几年已经克隆出一些控制孢原细胞分 化的基因, 如拟南芥中的 EXS/EMS1 [10][11] 、水稻中 MSP1 [12] 、玉米中 MAC1 [13] , 这些基因主要控制雄蕊 发育中造孢细胞的数量, 这些基因的突变将产生过 [14] 。Chapman [15] 认 为由小孢子本身产生的早期初生外壁提供了外壁发 育的模式, 指导着孢粉素物质的沉积。卢永根等 [16] 指出即使绒毡层发育正常, 适时地分泌孢粉素物质, 但如果小孢子本身异常, 无法提供外壁发育的模式, 致使孢粉素异常沉积, 同样会导致花粉败育。 绒毡层作为药壁的最内层, 对花粉发育的整个 过程有着重要作用, 绒毡层细胞的异常必然会影响 小孢子的正常发育。在花粉正常发育中, 绒毡层细 胞的适时解体是一种细胞程序化凋亡的过程, 这种 凋亡程序受严格的遗传信息调控 [17][18] 。谢潮添等 [19] 通过对白菜雄性不育的超微结构研究指出绒毡层的…”
unclassified